Association between Administration of Antithrombotics and Intraperitoneal Hemorrhage in Patients Undergoing Percutaneous Interventions for Liver Diseases - Asai, Akira (J Clin Med, 2021)
Currently, percutaneous interventions are essential for diagnosis and treatment of liver diseases. The most frequent complication of percutaneous interventions is intraperitoneal hemorrhage. Recently, the number of patients with liver diseases on antithrombotics has been increasing. This retrospective cohort study aimed to evaluate the risk factors for intraperitoneal hemorrhage in patients after percutaneous interventions for liver diseases. This study included 1025 patients who underwent percutaneous interventions for liver diseases from April 2015 to March 2020. All interventions were performed using an ultrasound-guided approach. The influence of antithrombotic drug administration in patients, who underwent percutaneous interventions according to the guidelines for the American Association for the Study of Liver Disease, was evaluated. Intraperitoneal hemorrhage after percutaneous interventions was detected by computed tomography. Intraperitoneal hemorrhage occurred in nine patients (0.88%); however, these adverse events were not severe. We compared clinical characteristics between the patients with and without intraperitoneal hemorrhage. Although, there was no difference based on the administration of antithrombotics (p = 0.1961), seven of nine patients who showed intraperitoneal hemorrhage received percutaneous treatments (radio frequency ablation or microwave ablation). Therefore, we divided patients who underwent treatments and liver biopsy and then investigated the influence of antithrombotics on the intraperitoneal hemorrhage. After propensity score matching in each patient group, the administration of antithrombotics was not identified as a risk factor for hemorrhage in patients who underwent interventional treatments and patients who underwent liver biopsy. When the antithrombotics were discontinued, according to the guidelines, it may not increase the risk factor for hemorrhage in patients of liver disease who underwent percutaneous interventions.